Spiritual resonance : polyphony and pneumatology in Dietrich Bonhoeffer’s late theology - Tarassenko, Joanna (Stellenbosch Theological Journal, 2023)
This article presents a pneumatological reading of Dietrich Bonhoeffer’s appeal to the phenomenon of musical resonance through his use of the metaphor of “polyphony” and related musical casts of mind. In so doing, it provides an alternative reading of Bonhoeffer’s late theology by establishing a connection between Letters and Papers from Prison and Ethics through his use of musical metaphors. In it I make two significant claims about Bonhoeffer’s use of musical metaphors in his late theology. First, that polyphony is a dynamic metaphor which Bonhoeffer discovers and utilises to express his understanding of the relationship between God and the world in Christ. I argue that the limitations of visual-spatial metaphors, which Bonhoeffer openly laments in Ethics, are overcome by his discovery of polyphony in Letters and Papers from Prison as a metaphor which conceptualises the relationship between God and the world (operating in a single realm or space) as well as preserving the distinction of each; in this respect, polyphony texturizes Bonhoeffer’s view of reality, carefully nuancing it. The way the metaphor functions for Bonhoeffer mirrors the way he employs the work of the Holy Spirit in his theology. Thus, it indicates that implicit in Bonhoeffer’s theological appeal to polyphony is a model of the agency of the Holy Spirit, so that in exploring polyphony a latent pneumatology in Bonhoeffer can be unearthed. Read in this way, polyphony is a potent metaphor for illumining the Spirit’s work as that which enables unity, distinction, and dynamic relationality between God and the world in the church. The article concludes by pointing to how a musico-pneumatology such as that which we find in Bonhoeffer can be further developed.